Timing of Flap Coverage With Respect to Definitive Fixation in Open Tibia Fractures. Issue 8 (August 2021) - Kuripla, Casey; Tornetta, Paul; Foote, Clary J.; Koh, Justin; Sems, Andrew; Shamaa, Tayseer; Vallier, Heather; Sorg, Debra; Mir, Hassan R.; Streufert, Benjamin; Spitler, Clay; Mullis, Brian; et al.
Abstract : Objectives: We conducted a large, U.S wide, observational study of type III tibial fractures, with the hypothesis that delays between definitive fixation and flap coverage might be a substantial modifiable risk factor associated with nosocomial wound infection. Design: A retrospective analysis of a multicenter database of open tibial fractures requiring flap coverage. Setting: Fourteen level-1 trauma centers across the United States. Patients: Two hundred ninety-six (n = 296) consecutive patients with Gustilo III open tibial fractures requiring flap coverage at 14 trauma centers were retrospectively analyzed from a large orthopaedic trauma registry. We collected demographics and the details of surgical care. We investigated the patient, and treatment factors leading to infection, including the time from various points in care to the time of soft-tissue coverage. Intervention: Delay definitive fixation and flap coverage in tibial type III fractures. Main Outcome Measurements: (1) Results of multivariate regression with time from injury to coverage, debridement to coverage, and definitive fixation to coverage in the model, to determine which delay measurement was most associated with infection. (2) A second multivariate model, including other factors in addition to measures of flap delay, to provide the estimate between delay and infection after adjustment for confounding. Results: Of 296 adults (227 M: 69 F) with open Gustilo type III tibial fractures requiring flap coverage, 96 (32.4%) became infected. In the multivariate regression, the time from definitive fixation to flap coverage was most predictive of subsequent wound infection (odds ratio 1.04, 95% confidence interval 1.01 to 1.08, n = 260, P = 0.02) among the time measurements. Temporary internal fixation was not associated with an increased risk of infection in both univariate ( P = 0.59) or multivariate analyses ( P = 0.60). Flap failure was associated with the highest odds of infection (odds ratio 6.83, 95% confidence interval 3.26 to 14.27, P < 0.001). Conclusion: Orthoplastic teams that are dedicated to severe musculoskeletal trauma, that facilitate coordination of definitive fixation and flap coverage, will reduce the infection rates in Gustilo type III tibial fractures. Level of Evidence: Therapeutic Level III. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.